2017
DOI: 10.1097/mnm.0000000000000713
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for the addition of prone imaging to myocardial perfusion single-photon emission computed tomography for inferior wall

Abstract: A decrease of the %uptake in segments 3, 4, 5, and 10 after supine imaging is presumed to result from attenuation artifact or RCA disease. We established evaluation criteria for the addition of prone imaging in patients with decreased accumulation in the inferior wall during supine imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Van Dijk et al studied 107 patients and found that CTAC lowers the need for additional rest imaging: attenuation correction rectified equivocal scans in more than 50% [6]. With respect to prone imaging, Nakaya et al showed that in conventional SPECT imaging the radiopharmaceutical uptake in inferior wall segments increased [16]. These findings were confirmed by Arsanjani et al and Nishina et al [17,18].…”
Section: Discussionmentioning
confidence: 94%
“…Van Dijk et al studied 107 patients and found that CTAC lowers the need for additional rest imaging: attenuation correction rectified equivocal scans in more than 50% [6]. With respect to prone imaging, Nakaya et al showed that in conventional SPECT imaging the radiopharmaceutical uptake in inferior wall segments increased [16]. These findings were confirmed by Arsanjani et al and Nishina et al [17,18].…”
Section: Discussionmentioning
confidence: 94%
“…A meta-analysis investigating the diagnostic performance of SPECT to detect ischemia-causing stenosis by FFR showed that in spite of the high specificity of 84%, the sensitivity was as low as 61% [10]. The low sensitivity of SPECT to detect FFR-positive stenosis was shown in other studies which ranged from 35% [15] or CT attenuation correction [13] [16] could be used to improve the diagnostic accuracy of the inferior wall. Also, Cadmium-Zinc-Telluride detector SPECT would be superior to the conventional anger SPECT because of its higher count sensitivity [17].…”
Section: Discussionmentioning
confidence: 99%
“…Despite their improved performance characteristics, cardiac CZT cameras are still considered to provide suboptimal specificity for identifying significant coronary artery disease (23), and attenuation artifacts potentially play a substantial role in this setting. Indeed, attenuation artifacts are at least as severe with Anger cameras as with CZT cameras (1) and, to date, are far from being fully prevented or detected by the various methodologies and strategies elaborated for this purpose (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to eliminate artifacts by imaging in the prone position have also been extensively reported (2,5,(9)(10)(11)(12)(13), with an efficiency not far from that obtained with the CT-based method for preventing inferior attenuation artifacts (5) and with the additional advantage of limiting certain breathing-related artifacts (cranial cardiac drift (12)). However, this method has the disadvantage of being somewhat uncomfortable and has been reported to produce anterior attenuation artifacts (11,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation